Forage accumulation and morphogenetic and structural characteristics of Megathyrsus maximus cv. Tamani under defoliation intensities - Costa, Newton (Pubvet, 2020)
Abstract. The effects of defoliation intensity (10, 20, 30 and 40 cm above soil level) on green dry matter (GDM) yield and morphogenetic and structural characteristics of Megathyrsus maximus cv. Tamani were evaluated under field conditions in Roraima´s savannas. The effects of defoliation intensity on the GDM yields, leaf area index and leaf elongation rates was adjusted to the quadratic regression model and maximum values recorded with cutting at 28.2; 33.3 and 21.6 cm above soil level, respectively. The population tiller density, number of leaves tiller-1 and leaf appearance rate was inversely proportional to the defoliation intensity, while the opposite occurred for to average leaf length and leaf senescence rate. Apical meristem removing percentage was higher with increasing defoliation intensity. Regrowth vigor showed close negative correlation with defoliation intensity. Pastures of M. maximus cv. Tamani managed under 25 to 30 cm residue provides higher forage productivity, larger efficiency of forage utilization, greater tissue renewal and canopy structure more favorable to grazing.Keywords: Green dry matter, leaves, tillering, senescence
Keywords: Green dry matter; leaves; tillering; senescence